2002
DOI: 10.1002/hep.1840360607
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microdialysis in patients with fulminant hepatic failure

Abstract: Fulminant hepatic failure (FHF) is often complicated by high intracranial pressure (ICP) and fatal brain damage. In this study, we determined if a rise in [glutamate]ec and [lactate]ec preceded surges of high ICP in patients with FHF (median age, 42; range, 20-55 years; 7 women; 3 men) by inserting a microdialysis catheter into the brain-cortex together with an ICP catheter. The microdialysis catheter was perfused with artificial cerebrospinal-fluid at a rate of 0.3 microL/min. Dialysate was collected approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 31 publications
0
39
0
2
Order By: Relevance
“…An increase in extracellular glutamate has been documented to be associated with severe HE (Michalak et al, 1996, Oria et al, 2012, Rose et al, 2007and Tofteng et al, 2002, and has been described to occur as a result of decreased mRNA and protein expression of astrocytic glutamate transporters (Desjardins et al, 2001, Knecht et al, 1997, Norenberg et al, 1997and Suárez et al, 2000. Subsequently, this is accompanied by a decrease in GS activity, but the continuous presence of high glutamine levels (Desjardins et al, 1999 andRao et al, 2005).…”
Section: Glutamine/glutamatementioning
confidence: 99%
“…An increase in extracellular glutamate has been documented to be associated with severe HE (Michalak et al, 1996, Oria et al, 2012, Rose et al, 2007and Tofteng et al, 2002, and has been described to occur as a result of decreased mRNA and protein expression of astrocytic glutamate transporters (Desjardins et al, 2001, Knecht et al, 1997, Norenberg et al, 1997and Suárez et al, 2000. Subsequently, this is accompanied by a decrease in GS activity, but the continuous presence of high glutamine levels (Desjardins et al, 1999 andRao et al, 2005).…”
Section: Glutamine/glutamatementioning
confidence: 99%
“…Chatauret et al (2001) found an increase in CSF lactate during severe encephalopathy and brain edema in rats with ALF. Clinically, extracellular brain lactate concentrations were found to increase in association with increased ICP in patients with ALF (Tofteng et al, 2002). It has also been demonstrated that alanine is elevated in the hyperammonemic brain (Hilgier et al, 1999;Mans et al, 1994;Swain et al, 1992) and more recently in rats with ALF using nuclear magnetic resonance (NMR) spectroscopy (Chatauret et al, 2003).…”
Section: The Pathophysiology Of Hypothermia-effect On the Brainmentioning
confidence: 99%
“…These observations may provide new insights into the pathogenesis of brain edema in ALF. Increased extracellular brain glutamate is a common finding in ALF [98], [99], [100] and [101]. Potential explanations include impairment of its clearance [102] and [103] and deregulation of calcium-dependent glutamate release from astrocytes [104].…”
Section: Extracellular Brain Concentrations Of Amino Acidsmentioning
confidence: 99%
“…Increased brain lactate is common in animal models [77], [93], [94] and [121], and peaks of lactate in brain microdialysate preceding surges of ICP have been described in patients with ALF [98]. Increased brain lactate correlated with worsening encephalopathy and intracranial hypertension in experimental models [92] and [121], and it was due to increased de novo synthesis from circulating glucose.…”
Section: Brain Glucose Metabolismmentioning
confidence: 99%